Corpus-based lexicographical descriptions with a special focus on pragmatics - Šorli, Mojca (ELOPE (Ljubljana), 2013)
The present paper focuses on ways in which the pragmatic (functional) meaning that arises from various contextual features, known in corpus linguistics as semantic prosody, can become an integral part of lexicographical descriptions as they are represented in the Slovene Lexical Database (SLD). This is particularly important for the treatment of phraseology and idiomatics. First, the theoretical background is provided, with the focus on the prototype theory and its practical implications for monolingual lexicography. A parallel is drawn with the model of meaning analysis in the SLD. The second part begins with a brief introduction to semantic prosody and continues with an analysis of monolingual meaning descriptions in the SLD against a number of authentic corpus examples, investigating how their pragmatic components have been identified. The analysis of corpus data shows that pragmatics is an important contributor to the process of sense discrimination in works of lexical and lexicographic relevance.
Keywords: frazeologija; leksikalna baza; leksikografski opisi; phraseology; pragmatika; semantična prozodija; Slovene; slovenščina